Development of Fraction Material Mathematics Module with Realistic Mathematics Education Learning Approach - Mardati, Asih; Febrilia, Yeyen (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2023)
This research aims to determine the steps of module development and the level of mathematics module fourth grade with realistic mathematics education learning approach quality. This research includes Research and Development (RnD) with the ADDIE development model. The object and subject in this research is the understanding of grade IV faction material in SD Negeri 2 Riau Silip. The instruments used are speech guidelines, expert assessments, and teacher responses, and student responses. The data analysis technique used qualitative and quantitative data. Qualitative data was analyzed from the results of testing the quality and validity of the module. The results of the research contain development steps, namely analysis stages, resistance to pressure, and resistance to development. The results of the assessments of media experts, material experts, learning experts and language experts obtained the following values of 85.3, 90.7, 80, and 80. While the results of the responses of fourth grade teachers and students were 100 and 92.8, the average assessment and expert validation test and the response of class IV teachers and students was 88.13 with the